An In-Depth Analysis of Lightweight Chassis Design for Electric Scooters Using Trellis Frame Structures - Goh, Ching Pang; Tan, Weng Chun (INTI International University, 2023)
Electric scooters are modules of electric vehicles with two wheels. They can be recharged from an external power source of electricity or by a rechargeable battery in the electric scooter. A lightweight chassis, also called the frame of an electric scooter, is the core structure that is in all this system of body electric scooters. Currently, the industry produces different types of electric scooters, but the project only focuses on electric scooters that are two-wheel-seated due to some of the chassis being in heavy condition. It may cause an accident in traffic. The purpose of this project is to study and analyses the common truss member structure of a lightweight chassis for electric scooters. The goal is to improve rider safety and reduce the weight of the frame structure. By designing a lightweight chassis with a trellis frame, we aim to achieve sufficient strength, rigidity, and durability while meeting design targets. To determine the force in each truss member, the method of jointing will be applied. This will help improve rider safety and reduce the weight of the frame structure. Five different design sketches of lightweight chassis with various common truss frames will be created using Computer-Aided Design (CAD) software. These designs will then be analyzed using ANSYS simulations, and the optimal chassis design will be determined based on the obtained findings and analysis. These simulations will help evaluate the performance and strength of the chassis designs under different conditions. By analyzing the results of the simulations, we can determine which design option is the most optimal for the electric scooter in terms of strength, rigidity, and durability